PECULIARITIES OF INTERACTIVE ACTIVITIES IN THE FOREIGN LANGUAGE TEACHING - Natalia V. Ageyenko; Alla A. Rybkina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article deals with the problem of training qualified specialists in the process of learning foreign languages. To solve this problem, interactive forms of learning promoting socialization of student are proposed. The article reveals the concept of "interaction", the essence of which depends on the social situation, behavior strategies and objectives of participants in the process of joint activities. The main objective of using interactive tasks is creation of conditions for self-realization of students in the course of communication. The authors consider the features of the interactive tasks based on cooperation and development of a uniform idea. The tasks of this sort include: ranging, guided discussion, and problem solving. Ranging is an exercise in which students are given a task to get acquainted with the offered material, to comprehend the information contained in this material and to distribute it according to some definite criteria. Authors also note that the guided discussion is based on a certain topic connected with the text. The exposition of discussion formulates a perspective as a certain substantial component which can be developed in polylogue discussion.